Comparative Analysis of Microbial Community Structure and Function in the Gut of Wild and Captive Amur Tiger - Ning, Yao; Qi, Jinzhe; Dobbins, Michael T.; Liang, Xin; Wang, Jingxuan; Chen, Shiyu; Ma, Jianzhang; Jiang, Guangshun (Frontiers in Microbiology, 2020)
It has been well acknowledged that the gut microbiome is important for host health, composition changes in these microbial communities might increase susceptibility to infections and reduced adaptability to environment. Reintroduction, as an effective strategy for wild population recovery and genetic diversity maintenance for endangered populations, usually take captive populations as rewilding resource. While, little is known about the compositional and functional differences of gut microbiota between captive and wild populations, especially for large carnivores, like Amur tiger. In this study, highthroughput sequencing of the 16S rRNA gene (amplicon sequencing) and metagenomics were used to analyze the composition and function variations of gut microbiota communities between captive and wild Amur tiger populations based on total 35 fecal samples (13 from captive tigers and 22 from wild tigers). Our results showed that captive Amur tigers have higher alpha diversity in gut microbiota, but that the average unweighted Unifrac distance of bacterial taxa among wild Amur tigers was much larger. The function differences involve most aspects of the body functions, especially for metabolism, environmental information processing, cellular processes and organismal systems. It was indicated that the diet habit and environment difference between captive and wild populations lead to composition differences of gut microbiota and then resulted in significant differences in functions. These contrasts of functional and compositional variations in gut microbiota between wild and captive Amur tigers are essential insights for guiding conservation management and policy decision-making, and call for more attention on the influence of gut microbiota on the ability of captive animals to survive in the wild.